A construção de "caixas" de marabaixo na comunidade quilombola do Curiaú : uma abordagem etnomatemática - Rodrigues, Quele Daiane Ferreira (2016)
This study aims to analyze how the mathematical knowledge involved in the making of marabaixo "drums" in the Quilombo community of Curiaú, located in the Municipality of Macapá, Amapá State, was generated, organized and disseminated. Regarding the exploratory nature of this research, in which no data can be sought that can be quantified, it assumes a qualitative ethnographic approach. It bases its theoretical basis on some assumptions that underpinned all research, they are: culture; Ethno; Ethnicity; Ethnomathematics. For the concept of culture the contributions of Tylor (1871), Geertz (1973), Laplantine (2007) and Herskovits (1973) were used. The concepts of ethno and ethnicity had as reference the productions of D'Adesky (2001) and Ferreira (2013). From the perspective of Ferreira (1997, 2013), Knijnik (2012), Barton (2002, 2006) and D'Ambrosio (1989, 1990, 1998, 2002, 2004, 2009) addresses Ethnomathematics, considering the definition of the Ethnomathematics Program given by D'Ambrosio as the most fruitful to address the theme and focus of this research. In order to compose the data for the analysis, we used semi-structured interviews with three artisans belonging to the community and observations. As a method of analysis, Moraes and Galiazzi (2011) guidelines on Discursive Textual Analysis were followed. It lists three a priori categories: Generation of knowledge; Organization of knowledge; Diffusion of knowledge. In relation to the knowledge generated in the making of the "drums", it recognizes that they arose from the concern of an active participant in the community not to allow this knowledge to be forgotten, knowledge that is not related to what is taught in school. The generation of thhis knowledge comes from the observation of their ancestors, and the practice from the teachings occurred within the community. It verifies in the organization of these knowledges the need for reorganization of those that were generated from father to son, due to the influences suffered in the political, economic and cultural environment, and the improvement of the raw material for the construction of the "drums". It shows that the diffusion is carried out from the realization of workshops to popularize the knowledge, and also the commercialization of the "drums" as a way of subsistence. Although artisans have a low level of schooling, they recognize the existence of mathematics in the making of the "drum", mainly related to the sales process and budget of the material to be used. However, by means of the observations it is verified that mathematical concepts such as cylinder, flat figures, area, volume and perimeter are present during the "drum" construction process. It ends by recognizing the role of the artisan in preserving the local culture, suggesting that such knowledge can be treated in school.